(untitled) (REMUNOM, 2024)
Introduction: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that can affect different organs and systems, presenting with different clinical manifestations. Classification and diagnosis are established based on observed signs and symptoms and laboratory analyzes of immunological markers. There are known correlations between these markers and the clinical manifestations listed in the SLE classification criteria, however, they have not yet been fully explored. Objectives: the objective of this study was to evaluate the association of serological markers of autoimmunity in patients diagnosed with SLE with the clinical manifestations present in the disease classification criteria. Methods: this is a cross-sectional, retrospective and observational study, based on electronic medical records of patients diagnosed with SLE in a specialized center in Cascavel-PR. A descriptive statistical analysis was conducted to evaluate the association between the presence and absence of different symptoms and the activity or absence of different antibodies. The Chi-square test of independence was applied, followed by the post-test of adjusted residuals, when necessary, and for the different manifestations, the exclusion criterion was considered for those that affected less than 35% of the sample considered. Only data with a p-value <5% were considered significant. Results: the only marker that showed an association (p<0.05) with the appearance of a symptom was “C3 and C4 consumed” with “non-scarring alopecia” (Ӽ2= 4.267; p= 0.039). Conclusion: the reduction of complement proteins may have a significant association with the clinical manifestation of non-scarring alopecia.